Investment Decision In Micro, Small And Medium Enterprises In Indonesia* - Siti Aisyah Tri Rahayu (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The purpose of this study are: First, to analyze is there any significant influence among debt ratio, internal capital, cash flow, inflation expectations and the expectations of rupiah exchange rate against the decisions of businessmen in the real sector to invest or not to invest; Second, to analyze the impact of the variables perception mortgage interest rates, perceptions of bank regulation, internal capital and cash flow on debt ratio of the real sector (leverage). Investment decision model is estimated using logit models. The results of regression estimates the overall good for business and risk analysis for financial risk shows that almost all explanatory variables in the equation are statistically significant. There are three variables have a positive influence on the investment decisions taken by the businesses i.e. the debt ratio, cash flow and exchange rate expectations.